Programming mobile devices : - Mikkonen, Tommi (John Wiley, 2007)
The book is a platform independent approach to programming mobile devices: it does not focus on specific technologies, and devices, instead it evaluates the component areas and issues that are common to all mobile software platforms. This text will enable the designer to programme mobile devices by mastering both hardware-aware and application-level software, as well as the main principles that guide their design.